2013
DOI: 10.1016/j.ijid.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PGL1 salivary IgA/IgM, serum IgG/IgM, and nasal Mycobacterium leprae DNA in individuals with household contact with leprosy

Abstract: We strongly suggest that serum IgG/IgM and salivary anti-PGL1 IgA/IgM measurements are used to follow leprosy household contacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…On the other hand, though less frequently occurring, seropositivity due to the presence of LID-1-specific anti-IgG may detect other samples only in the Gold-LFA. Furthermore, since leprosy patients may present only anti-PGL-I IgG and not IgM 22 the inclusion of detection of IgG specific for PGL-I in diagnostic tests for leprosy should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, though less frequently occurring, seropositivity due to the presence of LID-1-specific anti-IgG may detect other samples only in the Gold-LFA. Furthermore, since leprosy patients may present only anti-PGL-I IgG and not IgM 22 the inclusion of detection of IgG specific for PGL-I in diagnostic tests for leprosy should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…25 This is compatible with other findings showing that s-IgA levels were significantly higher in diabetic patients with periodontitis. 10,18,26 Using the gingival and modified sulcus bleeding indices, Malicka et al reported that the periodontal status of diabetic patients was significantly worse than that of healthy subjects. 12 Ranadheer et al showed that s-IgA levels were significantly higher among individuals with more than three DMFT.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all people exposed to the bacillus who develop anti-PGL-1 antibodies will develop clinical disease [22]. Few serological studies have been performed using anti-PGL-1 IgG [36][37][38][39]. The anti-PGL-1 IgM response is uniformly higher than IgG [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible anti-PGL-1 IgM can be detected in conditions that lead to polyclonal activation of lymphocytes, such as AIDS and psoriasis, even being detected in non-endemic regions [42]. False positives are known to occur in IgM detection due to the presence of rheumatoid factors [39]. In this context, the presence of IgG antibodies in the serum, reflects the safest form of exposure and re-exposure to the bacillus, since these antibodies represent the existence of memory cells at a secondary response moment to M. leprae [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation